Analysis of Asia-1 foot-and-mouth disease global spread in 1999–2019 - S. A. Kunikov; S. N. Fomina (Ветеринария сегодня)
In spite of current foot-and-mouth disease (FMD) preventive measures, the disease outbreaks are annually reported in different countries of the world. FMD tends to extensive spread and growing into epidemics. While being a transboundary infection according to the OIE/FAO classification, FMD severely affects the economy and international trade. The paper describes the analysis of the data on global spread of Type Asia-1 virus-induced FMD in 1999–2019. The virus of this type is most often reported in such Asian countries as Afghanistan, Pakistan, China, Nepal, Iran, Myanmar, from where it can spread to FMD free countries. In China, Asia-1 FMD outbreaks were reported from 2001 to 2009. Previously exotic for our country, the virus of this type was first reported in the Primorsky, Khabarovsk, Zabaikalsky Krais and Amur Oblast in 2005–2006. The results of the phylogenetic analysis of the recovered isolates demonstrated that FMD emergence in the Subjects of the Russian Federation was attributed to the virus introduction from the neighboring territories. Possible virus introduction from China resulted in significant economic expenditures on FMD containment and eradication. In view of the close trade and economic relations between the Russian Federation and such Asia-Pacific countries as China, India, Japan and Republic of Korea, one should place greater focus on the risk of FMDV introduction into the Russian Federation from these countries. Of key importance is intensification of the international cooperation with the Asian countries in the area of joint activities aimed at FMD freedom maintenance.